ANALISIS PENDAPATAN PEDAGANG DAGING SAPI DIPASAR TAVIP DAN PASAR KEBUN LADA BINJAI - Rianto, Ahmad; Media Agus Kurniawan, (Journal of Innovation Research and Knowledge, 2024)
The presence and existence of consuming beef in Indonesia is currently one of the benchmarks where beef is one of the basic needs that is much popular in society. In this research the analysis used is descriptive analysis. This qualitative analysis is used to discuss and explain the results of research on various symptoms which can be described in systematically arranged sentences. The income of beef traders at the Tavip traditional market and Kebun lada is IDR 50,240,000/day with an average of IDR 4,187,000/ day. Analysis of Return on Investment for beef traders at Tavip Market and Kebun Lada Market, namely the profit earned by traders is IDR 44,400,000 because the initial capital for selling meat is IDR 130,000/kg while the purchase price of raw materials is IDR. 90,000 and the total sales of all beef traders are 1110 kg/day. The total Return on Investment is 52% and the calculation of the business efficiency analysis of beef traders at Tavip Market and Binjai Lada Garden Market is by dividing total profit and revenue by total costs to obtain a calculation of IDR. 151,900,000: IDR 101,660,000 with the result obtained being 1.49 so that the R/C ratio is > 1, then the beef trading business is efficient and profitable.